The “Reform of the Century” of the Administrative Judiciary in Austria − a “New Era”also for the Administrative Jurisdiction in European Young Democracy States? - Chvosta, Peter (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The aim of the study is to present the assumptions and effects of the administrative judiciary reform in Austria in 2012 (Verwaltungsgerichtsbarkeits-Novelle 2012). This reform is referred to in Austria as the “reform of the century” because it was the result of the largest and most far-reaching change to the Austrian constitution since its entry into force in 1920. This reform was long debated, but due to the reluctance of Austrian politicians to reform in this area, it was in fact neither expected nor hoped for. The notion of “reform of the century” also reflects the amazement at the happy “window of opportunity” in Austrian politics, which allowed the implementation of this long-awaited reform. This formulation should not, however, obscure the fact that the reform of administrative judiciary in Austria was not a particular innovation in an international context: rather, it consisted in largely late adaptation to international standards, valid in other European countries many years earlier. Nevertheless, the reorganization of the legal protection system also includes changes which in fact constitute “new ground” in Austria. In the following parts of the study, after reviewing the historical development and the foundations and framework of the “new” administrative judiciary in organizational and procedural terms, the characteristics of the current system of legal protection in Austria are presented in more detail.